The application of acupuncture in cardiopathy: A bibliometric analysis based on Web of Science across ten recent years - Li, Xiao; Yin, Zihan; Ling, Fayang; Zheng, Qianhua; Li, Xiang; Qi, Wenchuan; Liang, Fanrong (Frontiers in Cardiovascular Medicine, 2022)
Background With high morbidity and mortality, cardiopathy is a major component of cardiovascular disease, causing a huge burden of disease to public health worldwide. In recent years, research on acupuncture treatment of cardiopathies has been increasing. However, no bibliometric analysis has been conducted to systematically describe the research progress and hotspots in this field. Therefore, this study aimed to conduct a bibliometric analysis of the relevant literature to explore the current status and future development of acupuncture for cardiopathies. Methods The Web of Science (WoS) Core Collection Database was searched for literature related to acupuncture therapies for cardiopathies from 2011 to 2021. Using CiteSpace 5.8 R3, cooperation network diagrams of authors, institutions, countries and journals, keyword co-occurrences, and clustering were performed and analyzed. Results A total of 321 studies were included. Overall, the number of annual publications increased yearly. These publications came from 31 countries or regions, of which China and the United States made the greatest contributions. In total, 333 authors from 258 institutions participated in this field, and Beijing University of Chinese Medicine and Professor Fanrong Liang were the most published institution and author, respectively. Evidence-based Complementary and Alternative Medicine published the largest number of articles, and CIRCULATION was the most commonly cited journal. Based on co-occurrences and cluster analysis of 257 keywords, three research frontiers and hotspots were identified: acupuncture for blood pressure regulation, acupuncture for coronary heart disease, and acupuncture for regulation of heart rate. In these three research frontiers, the rostral ventrolateral medulla (RVLM) and autonomic nervous system (ANS) are the most popular mechanisms. Conclusion A stable development trend has formed in this field. Further research should focus on the role of acupuncture therapies in the treatment of hypertension or hypertensive heart disease, coronary heart disease, and arrhythmia based on the mechanisms related to the RVLM and ANS.